Tumour necrosis factor microsatellites and HLA-DRB1*, HLA-DQA1*, and HLA-DQB1* alleles in Peruvian patients with rheumatoid arthritis. Issue 8 (1st August 2001) - Castro, F; Acevedo, E; Ciusani, E; Angulo, J A; Wollheim, F A; Sandberg-Wollheim, M
Abstract : OBJECTIVE: To study the association between rheumatoid arthritis (RA) and HLA and tumour necrosis factor (TNF) polymorphism in Peruvian mestizo patients in comparison with ethnically similar controls. METHODS: Seventy nine patients with RA and 65 ethnically matched healthy controls were genotyped for HLA-DRB1, HLA-DQA1, HLA-DQB1, and TNFα and TNFβ alleles using PCR amplification. Clinical severity was assessed as mild, moderate, or severe in 35 of the patients. RESULTS: TNFα6 showed the strongest association with disease susceptibility. The TNFα6 allele was more common in patients than in controls (p<0.0076) and the proportion of patients with at least one copy of this allele was greater (p<0.015, relative risk 2.35). Among the HLA-DRB1* alleles with the shared epitope sequence, only the DRB1*1402 allele was significantly increased in patients compared with controls (p<0.0311), as was the proportion of patients with at least one copy of this allele (p<0.0232, relative risk 2.74). In contrast, the overall frequency of alleles with the shared epitope was not different in patients and controls. The haplotype HLA-DRB1*1402-DQB1*0301-DQA1*0401 was significantly more common in patients. TNFα6 was more common in patients whether or not they had this haplotype. None of the 11 patients lacking the TNFα6 allele had severe disease. CONCLUSIONS: This study shows for the first time that TNF gene polymorphism is associated with susceptibility to RA in a non-white population. TNFα6 and HLA-DRB1*1402 independently conferred significantly increased risk in Peruvian mestizo patients.